Perancangan furnitur sebagai fasilitas belajar anak autisme yang mengimplementasikan prinsip Universal Design - Rhea Griselda; Purnama Esa Dora Tedjokoesoemo; Filipus Priyo Suprobo (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2022)
Education is an effort to improve human resource quality and growth in a country, especially for those who have disabilities. According to the Central Bureau of Statistics, in 2020, as many as 5% of Indonesia’s population are disabled. Autism is one of the pervasive intellectual disabilities in children that hinders the development of cognitive, language, behavior, communication, and social interaction. In 2019, the work vacancy for the disabled only covers 0.28% of the general job opportunity in Indonesia and further decreased by 0.1% in 2020. Therefore, to improve the human life quality of the disabled, an appropriate education system and facilities that apply Universal Design compliance to their needs were essential. The uses 5 steps of Design Thinking methods consist of Empathize, Define, Ideate, Prototype, and Test methods are hopefully will resolve the problem systematically, in detail, and accurately. The result produced multifunction furnitur by applying FURNURTURE, which stands for Furniture and Nurture, as the design concept. FURNITURE has several functions, namely; an education facility, a therapeutic facility, and storage by applying the Universal Design principle. Hopefully, the design, product, and design principles could stand as a model for other autism educational facilities and services.